A novel magnetic ZnFe2O4 aerogel photocatalyst for visible light reduction of Cr(VI) at high concentrations: Facile synthesis, enhanced activity and photocatalytic mechanism, combined with first-principles calculations. Issue 3 (1st February 2022) - Huang, Shun-tian; Tai, Ju-xiang; Hao, Wen-ke; Lu, Jia-xin; Liu, Si-jia; Wu, Xiao-dong; Cui, Sheng
Abstract: Herein, we prepared a novel magnetic ZnFe2 O4 aerogel capable of visible light reduction of Cr(VI) via the sol-gel method. The influences of different heat treatment temperatures on the physical phase, structure, and properties of the catalysts were systematically investigated. Photocatalytic experiments revealed that the 400 °C heat-treated ZnFe2 O4 aerogel exhibited the optimal photocatalytic performance. To attenuate the influence of catalyst adsorption on the photocatalytic experiments, the concentration of Cr(VI) solution was as high as 100 mg/L. The reduction rate of Cr(VI) was significantly higher than that of some previously reported ZnFe2 O4 photocatalysts after visible light irradiation for 120 min. A plausible photocatalytic reaction mechanism was deduced based on the first-principles DFT calculations and photoelectrochemical experiments. In addition, the 400 °C heat-treated ZnFe2 O4 aerogel possessed a high specific surface area of 115.31 m 2 /g and a saturation magnetization intensity of 10.6 emu/g, which allowed for recovery by magnetic separation.